Recanalization therapies for large vessel occlusion due to cervical artery dissection: a cohort study of the EVA-TRISP collaboration - Tränka, Christopher; Lorscheider, Johannes; Hametner, Christian; Baumgartner, Philipp; Gralla, Jan; Magoni, Mauro; Martinez-Majander, Nicolas; Casolla, Barbara; Feil, Katharina; Pascarella, Rosario; Papanagiotou, Panagiotis; Nordanstig, Annika; et al. (Journal of stroke, 2023)
Background and Purpose: This study aimed to investigate the effect of endovascular treatment (EVT, with or without intravenous thrombolysis [IVT]) versus IVT alone on outcomes in patients with acute ischemic stroke (AIS) and intracranial large vessel occlusion (LVO) attributable to cervical artery dissection (CeAD). Methods: This multinational cohort study was conducted based on prospectively collected data from the EVA-TRISP (EndoVAscular treatment and ThRombolysis for Ischemic Stroke Patients) collaboration. Consecutive patients (2015-2019) with AIS-LVO attributable to CeAD treated with EVT and/or IVT were included. Primary outcome measures were (1) favorable 3-month outcome (modified Rankin Scale score 0-2) and (2) complete recanalization (thrombolysis in cerebral infarction scale 2b/3). Odds ratios with 95% confidence intervals (OR [95% CI]) from logistic regression models were calculated (unadjusted, adjusted). Secondary analyses were performed in the patients with LVO in the anterior circulation (LVOant) including propensity score matching. Results: Among 290 patients, 222 (76.6%) had EVT and 68 (23.4%) IVT alone. EVT-treated patients had more severe strokes (National Institutes of Health Stroke Scale score, median [interquartile range]: 14 [10-19] vs. 4 [2-7], P<0.001). The frequency of favorable 3-month outcome did not differ significantly between both groups (EVT: 64.0% vs. IVT: 86.8%; ORadjusted 0.56 [0.24-1.32]). EVT was associated with higher rates of recanalization (80.5% vs. 40.7%; ORadjusted 8.85 [4.28-18.29]) compared to IVT. All secondary analyses showed higher recanalization rates in the EVT-group, which however never translated into better functional outcome rates compared to the IVT-group. Conclusion: We observed no signal of superiority of EVT over IVT regarding functional outcome in CeAD-patients with AIS and LVO despite higher rates of complete recanalization with EVT. Whether pathophysiological CeAD-characteristics or their younger age might explain this observation deserves further research.